Emprego de biopolímeros como forma de substituição a fontes de recursos naturais não renováveis - Rosalino, Natiely Cristiny Alves (Universidade Federal de São Carlos, 2023)
Due to its versatility and use in the most diverse areas of daily life, the production and consumption of plastic grew on a large scale from the 1970s onward (SCHWARZ, 1992) and still has a large market. However, for the most part, the origin of this material is through the use of fossil fuels, such as oil and mineral coal, being, therefore, of non-renewable origin and often non-biodegradable, which causes several problems to the environment. In this way, this study sought, through a bibliographical review of the subject, to highlight alternatives for the way of producing plastics, seeking to bring sustainable and less degrading forms to the environment. The conclusion whas that, despite the other alternatives already found for the production of plastic that does not use non-renewable sources, production through biopolymers, using biomass from cultures such as sugarcane and its derivatives, is in line with the that society needs to solve the plastic problem.
Use of biopolymers as a way to replace non-renewable natural resource sources
Keywords: Biodegradável; Polímeros de cana-de-açúcar; Biodegradable; Sugarcane polymers; CIENCIAS BIOLOGICAS::MICROBIOLOGIA